Pain pupillary index to prognosticate unfavorable outcome in comatose cardiac arrest patients. (July 2022) - Macchini, Elisabetta; Bertelli, Alessandra; Bogossian, Elisa Gouvea; Annoni, Filippo; Minini, Andrea; Quispe Cornejo, Armin; Creteur, Jacques; Donadello, Katia; Taccone, Fabio Silvio; Peluso, Lorenzo
Abstract: Background: The prognostic role of the Pupillary Pain Index (PPI), derived from automated pupillometry, remains unknown in post-anoxic brain injury. Methods: Single-center retrospective study in adult comatose cardiac arrest (CA) patients. Quantitative PPI and Neurologic Pupil Index (NPi) were concomitantly recorded on day 1 and day 2 after CA. The primary outcome was to assess the prognostic value of PPI to predict 3-month unfavourable outcome (UO, defined as Cerebral Performance Category of 3–5). Secondary outcome was the agreement between PPI and NPi to predict unfavourable outcome. Results: A total of 102 patients were included; patients with UO (n = 69, 68%) showed a lower NPi (4.2 [3.5–4.5] vs. 4.6 [4.3–4.7]; p < 0.01 on day 1–4.3 [3.8–4.7] vs 4.6 [4.3–4.8] on day 2), and PPI (3 [1–6] vs. 6 [3–7]; p < 0.01 on day 1–3 [1–6] vs 6 [4–8]; p < 0.01 on day 2) than others. A PPI = 1 on day 2 showed a sensitivity of 26 [95% CI 16–38]% and a specificity of 100 [95% CI 89–100]% to predict UO (p = 0.003 vs. NPi ≤ 2). On day 2, a total of 6 patients had concomitant PPI = 1 and NPi ≤ 2, while 12 showed NPi > 2 and PPI = 1; the coefficient of agreement was 0.42. Moreover, NPi and PPI values showed a moderate correlation both on day 1 and day 2. Conclusions: In this study, PPI = 1 on day 2 could predict UO in comatose CA patients with 100% specificity, but with a low sensitivity (yet higher than NPi). The agreement between PPI and NPi values was moderate.